Hydrothermal Carbonization of Biomass Waste for Solid Biofuel Production: Hydrochar Characterization and Its Application in Blast Furnace Injection - Guangwei Wang; Junyi Wu; Haibo Li; Andrey Karasev; Xiaojun Ning; Chuan Wang (Recycling)
Hydrothermal carbonization (HTC) technology converts biomass into a carbon-rich, oxygen-containing solid fuel. Most studies have focused on hydrochar produced under laboratory conditions, leaving a gap in understanding the performance of industrially produced hydrochar. This study comprehensively analyzes three types of industrially produced hydrochar for blast furnace (BF) injection. The results indicate that hydrochar has a higher volatile and lower fixed carbon content. It has a lower high heating value (HHV) than coal and contains more alkali matter. Nevertheless, hydrochar exhibits a better grindability and combustion performance than coal. Blending hydrochar with anthracite significantly enhances the combustion reactivity of the mixture. The theoretical conversion rate calculations reveal a synergistic effect between hydrochar and anthracite during co-combustion. Environmental benefit calculations show that replacing 40% of bituminous coal with hydrochar can reduce CO2 emissions by approximately 145 kg/tHM, which is equivalent to an annual reduction of 528 kton of CO2 and 208 kton of coal in BF operations. While industrially produced hydrochar meets BF injection requirements, its low ignition point and high explosivity necessitate the careful control of the blending ratio.